Microwave activated desulfurization of turkish coals and lignite, şirnak asphaltite - micro selective coagulation in modified tube settling seperator - Tosun, Yıldırım İsmail (ITU Mineral Processing Engineering Department and the Turkish Mining Development Foundation, 2017)
Clean coal products of Tunçbilek, Bolu Mengen, Kütahya Gediz lignite, Sirnak asphaltite were received as mid-products and shale settlements in modified tube settler in the column form. The cleaner products was also second cleaning stage was also carried out. Heavy duty washing was applied in two and three stages ranging 1.5 to 1.7 gr/cm3 densities of ZnCl2 baths in order to determine and compare with Tube settler performance and cleaning efficiencies of coagulation and settling. The modified settler design for the optimum washing unit for the most advanced clean product was investigated. With the advanced design, the best quality lignite is obtained by producing the cleanest product that the country needs as desulfurization. The coal types can change the method of coagulation cleaning of the coal and asphaltite in the local area of Şırnak. The country side may use much simple methods using water settling and during settling coagulation of asphaltite fines as clean desulfurized products. This method could be successful in high product yield for mid products and pyrite rejection following Humphrey spirals. The combustion yields for Şırnak asphaltite fine under 100 micron was over 73% and 60% with 23% ash and 22% ash contents in the first and last cleaning stage end, respectively. Microwave act was determined by keeping the samples in microwave oven in the laboratory for 10 to 3 minutes for just surface modification of coal pyrite. 3 minute acted coal samples desulfurization at cleaning stages was reached 55% for Şırnak asphaltite fine while the desulfurization rate values was 44% in control tests of selective coagulation tests.
Keywords: Selective Coagulation; Modified Settler; Cleaning Coal; Desulfurization; Washing Asphaltite